PENGUKURAN MINAT BELAJAR SISWA KELAS XI SMA DALAM PROSES PEMBELAJARAN MATEMATIKA - Aditya, Muhammad Surya; Imami, Adi Ihsan (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to determine how well the level of interest in mathematical learning of students in mathematics subjects in terms of indicators of learning interest. The subjects in this study were one of class XI at SMA Negeri 6 Karawang for the 2023/2024 academic year, totaling 29 students. This research was conducted using a descriptive method with a qualitative approach. Data collection was obtained with a non-test instrument in the form of a mathematical learning interest questionnaire consisting of 22 statements and adjusted based on indicators of learning interest. After processing data using the Likert scale, the happy indicator has a percentage of 62% (good), the student interest indicator is at 70% (good), the indicator of student attention to the criteria is quite good at 54%, and the student engagement indicator has good criteria with a percentage of 64%. From the results of the study, it can be concluded that the level of interest in learning students in mathematics learning has a good level overall, in terms of indicators of learning interest, namely feelings of pleasure, student interest, student attention, and student involvement.